2016
DOI: 10.1002/2327-6924.12246
|View full text |Cite
|
Sign up to set email alerts
|

A primary care intervention to improve weight in obese children: A feasibility study

Abstract: Purpose Examine the effects of a primary care weight management program, which used a parent–child–provider collaborative negotiation intervention, among rural‐dwelling families with obese children. Data sources Health histories, physical examinations, fasting blood samples, interviews, and questionnaires. Conclusions Feasibility of implementing a family weight management intervention in a rural primary care setting was demonstrated. Few differences between the treatment and comparison groups were found; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Meta‐analysis of the intervention arms from nine studies, with a combined sample of 491 participants, found no change in ED risk post‐intervention (Figure A; SMD [SE], −0.10 [0.10], P = 0.317, I 2 86%). A follow‐up measure of up to 4.6 years from baseline was reported in six studies, with a combined effect of −0.31 [0.13], P = 0.012, I 2 88% (Figure B) representing a reduction in ED risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta‐analysis of the intervention arms from nine studies, with a combined sample of 491 participants, found no change in ED risk post‐intervention (Figure A; SMD [SE], −0.10 [0.10], P = 0.317, I 2 86%). A follow‐up measure of up to 4.6 years from baseline was reported in six studies, with a combined effect of −0.31 [0.13], P = 0.012, I 2 88% (Figure B) representing a reduction in ED risk.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, 18 articles reported on noncontrolled trials (pre-post), [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 17 on randomized controlled trials, [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and one on a nonrandomized controlled trial. 54 Studies were conducted in the United States, 19,32,33,42,[44][45][46][47]52,53 Belgium, [20][21][22]35,36,…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This included ethnic groups identified as being at risk (Marion, Finnegan et al 2009, Choi and Rush 2012, Barrett , Salem et al 2015, Murphy, Coke et al 2015, individuals and groups from rural areas (Wright, Purdy et al 2007, Jessee and Rutledge 2012, Murfet, Allen et al 2013, Barrett , Salem et al 2015, Kozlowski, Lusk et al 2015, Tokuda, Lorenzo et al 2016, Tyler and Horner 2016, areas of socio-economic disadvantage (Speck, Hines-Martin et al 2007, Marion, Finnegan et al 2009, Lynam, Loock et al 2010, Stines, Perman et al 2011, Wong, Lynam et al 2012, Walker, Marshall et al 2013, Ritten, Waldrop et al 2015, Berry, Williams et al 2016 or frail elderly (Wajnberg, Wang et al 2010, Prasad, Dunn et al 2014, Ritchie, Andersen et al 2016. In this way, nurse practitioners practiced to improve the health of hard to reach populations challenged with access and acceptability of traditional health care services.…”
Section: Who Do Nurse Practitioners Work With?mentioning
confidence: 99%
“…Most of this work related to specific disease processes such as asthma (Newcomb 2006, Allcock 2009), concomitant asthma and sickle cell disease (McClain, Ivy et al 2016), anxiety (Kozlowski, Lusk et al 2015), or eczema (Schuttelaar, Vermeulen et al 2009). Five programs were broader, including rehabilitative, preventive and some promotive aspects in obesity (Perman 2008, Stines, Perman et al 2011, Tyler and Horner 2016, parental functioning (Ordway, Sadler et al 2014), access to health care for vulnerable children (Lynam, Loock et al 2010, Wong, Lynam et al 2012) and wellbeing of runaway adolescent girls (Edinburgh and Saewyc 2009). …”
Section: Who Do Nurse Practitioners Work With?mentioning
confidence: 99%